PENGARUH MANAGEMENT ASSURANCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA MANAJERIAL PT SAT NUSAPERSADA - Seila Zera; Erni Yanti Natalia (LPPM Universitas Putera Batam, 2025)
This study aims to determine the extent to which management assurance and accounting information systems influence managerial performance at PT Satnusa Persada. The research was motivated by the company’s need to improve decision-making effectiveness and operational efficiency amid the challenges of the manufacturing industry. The method employed is a quantitative approach, with data collected through questionnaires distributed to 80 respondents consisting of managers and staff at PT Sat Nusapersada. The independent variables are management assurance and accounting information systems, while the dependent variable is managerial performance. The results of multiple linear regression analysis show that both independent variables have a positive and significant effect—both partially and simultaneously—on managerial performance. These findings highlight the crucial role of management assurance in ensuring accountability and organizational effectiveness, as well as the importance of accounting information systems in providing relevant and accurate financial data for strategic decision-making. This research provides practical implications for internal policy formulation and serves as a theoretical reference for future studies in the field of management accounting.